An Agent-Based Framework for Complex Networks - Wendt A.; Götzinger M.; Sauter T. (My University, 2022)
A large number of research and industrial projects could benefit from a module-based development. However, these modules and the communication between them may vary from project to project. Therefore, a general middleware instead of several specialized middlewares for each domain is desired. This paper presents the ACONA Framework (Agent-based Complex Network Architecture). It is an agent-based middleware with a lightweight and flexible infrastructure. Also, it offers the possibility of evolutionary programming. Its performance is demonstrated in three applications: (i) A cognitive architecture with around 40 interconnected modules; (ii) a stock market simulator with elements of evolutionary programming; and (iii) an industry 4.0 application of a conveyor belt.
Artificial Intelligence Applications and Innovations : 15th IFIP WG 12.5 International Conference, AIAI 2019, Hersonissos, Crete, Greece, May 24–26, 2019, Proceedings